Variasi Penggunaan Limbah Crushing Plant Bijih Besi Gunung Batu Sebagai Agregat Halus Terhadap Mutu Beton: Variation In The Use Of Stone Mountain Iron Ore Crushing Plant Waste As Fine Aggregate On The Quality Of Concrete - Dewi Yuniar; Fitriansyah Fitriansyah; Adi Susetyo Dermawan; Hadi Surya Wibawanto Sunarwadi; Teten Suparto (Media Ilmiah Teknik Sipil, 2023)
The increasing demand for concrete as a construction material has resulted in the depletion of natural resources. This motivates the construction industry to continue to innovate in the manufacture of concrete. The utilization of iron ore waste as a substitute for fine aggregate is one of the solutions. This study aims to determine the optimum composition of iron ore waste as a substitute for fine aggregate on compressive test strength and economic value of concrete mix materials. This study used coarse aggregate from the quarry location of Mount Batu PTP Pelaihari District, Tanah Laut Regency, fine aggregate from the iron ore crushing plant location from the stockpile of Perusda Baratala and ex. Palangkaraya. The testing at the UPT Construction Material Testing Laboratory DPUPRP Tanah Laut Regency, South Kalimantan Province. The results showed that concrete using fine aggregate/sand ex. Palangkaraya has a concrete quality of K-235.94 kg/cm2 or fc'= 19.583 Mpa. As a result, it was found that the concrete mixes were more efficient than the concrete mixes used in the concrete batching plant, and that the concrete mixes were more efficient than the concrete mixes used in the concrete batching plant AK (Coarse aggregat) 54%: AH (fine aggregates) 45% has a concrete quality of K-257.29 kg/cm2 or fc'= 22.849 Mpa. This shows that iron ore waste fine aggregate can be used in concrete mixes